2016
DOI: 10.3892/or.2016.4901
|View full text |Cite
|
Sign up to set email alerts
|

SEMA3B improves the survival of patients with esophageal squamous cell carcinoma by upregulating p53 and p21

Abstract: As one of the most common malignancies, esophageal squamous cell carcinoma (ESCC) is ranked as the sixth leading cause of cancer-related death worldwide. In our previous study, by employing cDNA microarray analysis, semaphorin 3B (SEMA3B) was found to be significantly downregulated in ESCC. In the present study, SEMA3B downregulation at the mRNA level was found in 34 of 60 primary ESCCs (56.7%) and in 6 of 9 ESCC cell lines (66.7%) by transcription-polymerase chain reaction (RT-PCR). Moreover, immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Our results were consistent with those reports implying the positive prognostic role of elevated p21 expression in ESCC. 7,8,[10][11][12][13] However, several other reports suggested an adverse prognostic role of up-regulated p21 expression for ESCC patients. 5,6,9 The inconsistency among these studies is most likely due to inadequate study design, limited populations with different geographic locations, or even different esophageal cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were consistent with those reports implying the positive prognostic role of elevated p21 expression in ESCC. 7,8,[10][11][12][13] However, several other reports suggested an adverse prognostic role of up-regulated p21 expression for ESCC patients. 5,6,9 The inconsistency among these studies is most likely due to inadequate study design, limited populations with different geographic locations, or even different esophageal cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…In close agreement with our findings, studies in adipocytes found that half-maximal Akt1 cellular signaling activity is achieved when the kinase is 5–22% phosphorylated [ 13 ]. In studies of human tumors [ 12 , 13 , 14 , 15 ] and in clinical diagnostic settings [ 14 , 15 ], the phosphorylation status of Akt1 at Ser473 only is often used as a marker or proxy for Akt1 activity. Our work [ 12 ] and work by others [ 16 ] found that phosphorylation of Thr308 alone was sufficient for maximal Akt1 signal prorogation in cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among the members of these signaling pathways, we noticed the SEMA3B gene. First, the microarray results suggested that SEMA3B was significantly altered in the chip, and it is included in the Axon guidance pathway and the Neuroscience pathway found by pathway analysis . Moreover, the SEMA3B gene was thought to play an important role in regulating cellular senescence and apoptosis .…”
Section: Discussionmentioning
confidence: 99%